Recombinant VP1 protein of norovirus GII.4 (Caliciviridae: Norovirus) is capable to induse the production of cross-reacting antibodies - Vladislav A. Lapin; Dmitry V. Novikov; Alexander Yu. Kashnikov; Natalia V. Epifanova; Nadezhda A. Novikova; Ekaterina V. Mokhonova; Dmitry A. Melentev; Maria I. Tsyganova; Dmitry E. Zaitsev; Viktor V. Novikov (Вопросы вирусологии)
Introduction. Norovirus (NoV) is one of the main causes of acute gastroenteritis. Currently, there is no vaccine to prevent norovirus infection. Vaccines under development are based on the capsid protein VP1, which is capable of forming virus-like particles.